Pencantuman Klausula Ahli Waris dalam Perjanjian Kredit Dikaitkan dengan Asas Kepribadian - Muhammad Nur Alamsyah; Vazrie Avicenna; Gusti Yosi Andri (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2025)
The heirs' clause in the credit agreement raises legal problems because it concerns the attachment of third parties. This study aims to analyze the inclusion of heirs' clauses based on privity of contract and its legal implications for legal protection for creditors and heirs. Normative juridical method has used with regulatory and conceptual approach. The results shown that the heir's attachment clause in a credit agreement does not necessarily bind the heirs automatically because the privity of contract limits the engagement only to the parties who made the agreement. This is based on the existence of the principle of saisine in Civil Law and the principle of ijbari in Islamic Law where the heir automatically becomes the owner of the heir's legacy. However, the attachment that arises is only limited to the management of heritage property before it is distributed as inheritance. The applicability of the clause must also take into account whether there is an inheritance by the heirs, because the liability for the heir's debts only arises if the inheritance is received. If the inheritance is rejected, the creditor cannot impose payment obligations on the heirs even though there is an attachment clause. On the other hand, Islamic Law has emphasized that inheritance received by heirs is only inheritance that has been reduced by burdens, including the heir's debt. Therefore, the inclusion of the heir's clause is only a notification that reminds the heirs that there are still unfulfilled heirs' obligations, namely debts.